CONVERSATIONAL IMPLICATURE IN RAJA AL-SANEA’S NOVEL BANAT AL-RIYAD (A Content Analysis) - Dedie Rusmiadie (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
Abstract Objective of this study is to gain understanding about types of implicature and violation of cooperative Maxim in Rajaa Al Sane's novel The Girl of Riyadh. The study took place between August, 2016 and March, 2017. The study was a qualitative study with content analysis method, which involved data collection, data processing, data analysis and data display. The focus of this study was analyzing two types of implicatures used in utterances in the novel, namely conventional and non-conventional implicature as well as violations of Grice's Cooperative Principles resulting in implicature, namely Maxim of quantity, Maxim of relevance, Maxim of manner, Maxim of relevance-quality, Maxim of quantity-quality and Maxim of quantity-manner. The findings of this study have theoretical contributions to Arabic learning theories in university, in general and provide examples of foreign language implicatures, in particular. Keywords: Conventional Implicature, Conversational Implicature, Violation of Cooperative Maxim